Economic valuation of high natural value areas in Central Roztocze - Grażyna Gawrońska; Krzysztof Gawroński; Dorota Dymek; Edward Sankowski; Betty Harris (Acta Scientiarum Polonorum. Formatio Circumiectus)
The paper discusses and analyses some basic issues about economic valuation of high natural value areas. As a concrete illustration, but also to enable an account of some central general topics, the paper also deals with the valuation of high natural value areas in Central Roztocze. The valuation was performed using the individual travel cost method. The valuation was carried out on the basis of results of a survey (n = 323) and statistical data. The calculation includes the travel cost, the costs of accommodation, the costs spent on special equipment rental and other costs associated with the visit to the study area. Moreover, the calculation takes into account the information about the amount of time respondents spent in the study area and information about the total number of visitors per year to the study area. The determined total travel cost was PLN 66.861. The average individual travel cost per one user amounted to PLN 207. In order to determine the total value of the high natural value areas of Central Roztocze it was necessary to combine the number of tourists visiting the site during the year and the average cost of travel. The total number of visitors per year is 750.000. The calculations show that the total economic value (understood as defined here) of the high natural value areas in Central Roztocze is PLN 155.250.000.